Penerapan Analisis volume biaya keuntungan sebagai Alat Perencanaan Keuntungan Jangka Pendek Di Kawasan Hutan Hijau Resort Bandung - Andi Azizah Ramadhani; Dewi Andriani; Riska Veronika (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2018)
This study was conducted to determine how much the influence of cost and sales volume to the profit. The Green Forest Resort Bandung has not applied the Cost Volume Profit analysis as tool in decision making of profit planning. This is a quantitative descriptive research, provides an overview calculation of systematic, precise, and accurate information data. The data obtained by conducting interview to the hotel, documentation study, and also literature study. Basic assumption in the analysis of Cost Volume Profit is all expenses should be classified as fixed costs and variable costs. Thus, in this research, the writer uses Multiple Allocation Basic Approach (MABA) method and Least Squares Regression Method to perform the allocation and separation of fixed costs and variable costs. The elements are: Break Even Point, Contribution Margin, Operating Leverage, and Margin Of  Safety. Research analysis found that total costs of Green Forest Resort Bandung is exceeds the breakeven point which indicating poor condition. Meanwhile, contribution margin is in good condition because it covers the fixed costs, although monthly amount of operating profit generated is small. Moreover, although during October and November the operating leverage and margin of safety are not optimum but they revealed a good condition. Some recommendations can be proposed to the hotel management, particularly for accounting department in The Green Forest Resort Bandung in order to be able to classified the costs into fixed costs and variable costs, and using the analysis calculations of Cost Volume Profit Analysis to support  the planning of a proper profit.Keywords:Cost Volume Profit, Multiple Allocation Basic Approach, Green Forest Resort